Asymmetric Split‐Gate Ambipolar Transistor and Its Circuit Application to Complementary Inverter. Issue 4 (17th May 2016) - Yoo, Hocheon; Smits, Edsger C. P.; van Breemen, Albert J. J. M.; van der Steen, Jan‐Laurens P. J.; Torricelli, Fabrizio; Ghittorelli, Matteo; Lee, Jiyoul; Gelinck, Gerwin H.; Kim, Jae‐Joon
Abstract : Using a concept of asymmetric side gate and main gate, it is shown that it is possible to realize unipolar transport (both p‐type and n‐type) in a thin‐film transistor with a high‐performance ambipolar polymer semiconductor. In a complementary inverter, this results in higher noise margin and DC gain.